Modelling and small-signal analysis of a grid connected doubly-fed induction generator - Mei,F; Pal,BC (IEEE USA, 2005)
This paper describes the modeling and small signal analysis of a grid connected doubly-fed induction generator(DFIG). Different models are formulated and compared witheach other for different assumptions (two or one-mass drive train,with or without stator transients). The models are developedfrom the basic flux linkage, voltage and torque equations.Eigenvalues and participation factor analysis of the linearizedmodels are carried out to relate the DFIG electromechanical modes to its relevant state variables.